1971
DOI: 10.1063/1.1685045
|View full text |Cite
|
Sign up to set email alerts
|

A Free-Space Focused Microwave System to Determine the Complex Permittivity of Materials to Temperatures Exceeding 2000°C

Abstract: The instrumentation, the design of the free-space focused microwave bridge system, and the technique for determining the complex permittivity of materials from ambient to 2500°C are described. The system employs a rotating disk sample which is located at the coincident focal point between two prolate spheroidal reflectors; the sample is heated on one side by oxyacetylene flames in such a manner that the microwave beam is not affected by the flames. Dynamic measurements are made of the sample insertion phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…He reported that free-space methods are non-destructive and contactless techniques which are specially suited for dielectric measurement of materials. In 1971, Harold L. Basset [2] was the first researcher to measure complex permittivity in free-space using spot-focusing antennas at a frequency of 9.4 GHz. He measured complex permittivity of fused silica as a function of temperature from ambient to 2500 C.…”
Section: Measurement Methods XXmentioning
confidence: 99%
“…He reported that free-space methods are non-destructive and contactless techniques which are specially suited for dielectric measurement of materials. In 1971, Harold L. Basset [2] was the first researcher to measure complex permittivity in free-space using spot-focusing antennas at a frequency of 9.4 GHz. He measured complex permittivity of fused silica as a function of temperature from ambient to 2500 C.…”
Section: Measurement Methods XXmentioning
confidence: 99%
“…1, 2 The spot-focusing horn lens antennas were used for minimizing diffraction effects due to the edges of the sample. [1][2][3][4][5][7][8][9] The incident wave projected by a spot-focusing horn lens antenna into the sample approximates a Gaussian beam, [11][12][13] as shown in Fig. 1, so the incident wave illuminating on the surface of the planar sample is not the wave of free-space actually.…”
Section: Introductionmentioning
confidence: 99%